Gender Differences of Final Height Contributed by Parents’ Height Among Healthy Individuals - Pen-Hua Su; Shu-Li Wang; Jia-Yuh Chen (Pediatrics and Neonatology)
Estimation of children’s final height is of great interest for pediatric endocrinologists in diagnosing and evaluating the treatment of short stature. The current study was performed to characterize the feature of offsprings’ final heights by their parents’ heights by gender in Taiwan. Methods: Healthy participants aged 25–35 years who underwent health examinations were recruited for body height measurements with standard processes regulated by a protocol and were enquired about their parental peak adult heights in 2003–2004. Differential contributions from each parent to the tallest/shortest child’s height in the family were then assessed with simple linear regressions with scatter plots by gender. Meanwhile, statistical comparisons with the corrected midparental height method and final height for parental height model were performed. Results: A total of 1113 male and 1036 female participants were enrolled. The fathers’ height contributed the most to the tallest son’s height in the family (adjusted R2=0.20), and mother’s height contributed the most to the shortest daughter’s height in the family (adjusted R2=0.18). Specifically, the final height for parental height line worked better for the contribution of midparental height to the tallest son’s height in prediction. Conclusions: For clinical practice, our results provided a reasonable estimation of final heights among local Taiwanese population and are also applicable for the evaluation of growth hormone replacement therapies for patients with short stature of non-growth-hormone defect.